Interprofessional learning in immediate life support training does effect TEAM performance during simulated resuscitation. (1st December 2018) - Morse, Jeremy Charles; Brown, Craig William; Morrison, Ian; Wood, Caroline
Abstract : Aim of the study: To assess performance in a simulated resuscitation after participating in either an interprofessional learning (IPL) or uniprofessional learning (UPL) immediate life support (ILS) training course. Introduction: The Team Emergency Assessment Measure (TEAM) is routinely used in Resuscitation Council (UK) Advanced Life Support courses. This study used the psychometrically validated tool to assess if the delivery of an IPL ILS to final year medical and nursing students could improve overall behavioural performance and global TEAM score. Methods: A randomised study of medical (n=48) and nursing (n=48) students, assessing performance in a simulated resuscitation following the IPL or UPL ILS courses. Postcourse completion participants were invited back to undertake a video-recorded simulated-resuscitation scenario. Each of these were reviewed using the TEAM tool, at the time by an experienced advanced life support instructor and subsequently by a clinician, independent to the study and blinded as to which cohort they were reviewing. Results: Inter-rater reliability was tested using a Bland-Altman plot indicating non-proportional bias between raters. Parametric testing and analysis showed statistically significant higher global overall mean TEAM scores for those who had attended the IPL ILS courses. Conclusion: Our results demonstrate that an IPL approach in ILS produced an increased effect on TEAM scores with raters recording a significantly more collaborative team performance. A postscenario questionnaire for students also found a significantly improved experience within the team following the IPL course compared with those completing UPL training. Although this study shows that team behaviour and performance can change and improve in the short-term, we acknowledge further studies are required to assess the long-term effects of IPL interventions. Additionally, through this type of study methodology, other outcomes in regard to resuscitation team performance may be measured, highlighting other potential benefit to patients, at level four of Kirkpatrick's hierarchy.